OPTIMIZATION OF TENSILE STRENGTH OF EMPTY OIL PALM FRUIT BUNCH FIBER REINFORCED COMPOSITES USING GENETIC ALGORITHMS - Rahim, Abdul; Mujianto, Agus; Feriyanto, Richie; Waloyo, Hery Tri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The use of natural materials such as oil palm empty fruit bunch fibers can provide a solution to increase value-added and manage plantation waste. Fibers are combined with a matrix to create composite materials. Instead of glass fibers, environmentally friendly natural fibers serve as the reinforcement in the composite material. Implementing natural fiber composites must consider the primary construction requirement, which is tensile strength. Artificial intelligence like genetic algorithms (GA) can simplify and reduce costs in the search for optimal values in composite material engineering. Data is obtained through experimental testing prepared samples and subsequently used as input for GA. The input parameters consist of three variables such as soaking time, volume fraction, and fiber length. The output of the optimization process is tensile strength. The maximum tensile strength has already been achieved with genetic crossover by the 125th generation. Based on GA calculations, the optimal parameters obtained are soaking time of 6.2 hours, volume fraction of 29.6%, and fiber length of 6.9 cm. The predicted optimal tensile strength value is 4.78 MPa.